ВЗАЄМОДІЯ НАЦІОНАЛЬНОГО АНТИКОРУПЦІЙНОГО БЮРО УКРАЇНИ З ІНШИМИ ДЕРЖАВНИМИ ОРГАНАМИ: ОСОБЛИВОСТІ ТА КЛАСИФІКАЦІЯ - Скомаров, Олександр Вікторович (SUPREMANCE OF LAW, 2017)
The article shows the features of the interaction between National Anti-Corruption Bureau of Ukraine and other governmental institutions while conduction of the activities aimed at identification, cessation, investigation and disclosure of the corruptive perpetrations, made by officials, authorized for accomplishment of governmental functions. A term “interaction” was analyzed as a pragmatic and applied category. Based on the research conducted, a classifi cation of the interaction between the National Anti-Corruption Bureau of Ukraine and other governmental institutions, depending on the spheres of appliance, features of the procedures of involvement in interaction, and duration of inter-authority relations, was suggested.